2015
DOI: 10.1177/0014402914563700
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Academic Achievement of Deaf and Hard-of-Hearing Students From Individual, Household, Communication, and Educational Factors

Abstract: Research suggests that the academic achievement of deaf and hard-of-hearing (DHH) students is the result of a complex interplay of many factors. These factors include characteristics of the students (e.g., hearing thresholds, language fluencies, mode of communication, and communication functioning), characteristics of their family environments (e.g., parent education level, socioeconomic status), and experiences inside and outside school (e.g., school placement, having been retained at grade level). This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 150 publications
(109 citation statements)
references
References 46 publications
6
85
0
7
Order By: Relevance
“…These findings might appear surprising, given the literature indicating significant benefits of cochlear implantation for young deaf children. Nevertheless, they are convergent with a variety of recent findings indicating that the early advantages in reading of CI users relative to nonusers-like those of deaf children having deaf parents compared to having hearing parents-are diminished or disappear by high school age Geers, Tobey, Moog, & Brenner, 2008;Marschark, Shaver, Nagle, & Newman, 2015;see Marschark & Leigh, 2016, for a review). Both situations could be the result of the increasing complexity of materials and differing goals of reading at the high school level (Archbold, 2015), premature cessation of interventions for deaf children who show age-appropriate language and reading skills in elementary school (Nittrouer & Caldwell-Tarr, 2016), or because those skills are increasingly mediated by other factors, such as quality of communication (H. Knoors, personal communication, May 19, 2016).…”
Section: Relations Among Communication Social Maturity and Executivsupporting
confidence: 78%
See 1 more Smart Citation
“…These findings might appear surprising, given the literature indicating significant benefits of cochlear implantation for young deaf children. Nevertheless, they are convergent with a variety of recent findings indicating that the early advantages in reading of CI users relative to nonusers-like those of deaf children having deaf parents compared to having hearing parents-are diminished or disappear by high school age Geers, Tobey, Moog, & Brenner, 2008;Marschark, Shaver, Nagle, & Newman, 2015;see Marschark & Leigh, 2016, for a review). Both situations could be the result of the increasing complexity of materials and differing goals of reading at the high school level (Archbold, 2015), premature cessation of interventions for deaf children who show age-appropriate language and reading skills in elementary school (Nittrouer & Caldwell-Tarr, 2016), or because those skills are increasingly mediated by other factors, such as quality of communication (H. Knoors, personal communication, May 19, 2016).…”
Section: Relations Among Communication Social Maturity and Executivsupporting
confidence: 78%
“…Recent research (see Archbold, 2015;Harris, 2016, for reviews) has demonstrated significant benefits of cochlear implantation to young deaf children's speech and language, school achievement, and social-emotional functioning (the last usually according to parent reports). Benefits to achievement, however, largely have been found to disappear by high school and college age (Geers & Hayes, 2011;Geers et al, 2008;Harris & Terlektsi, 2010;Marschark, Shaver et al, 2015), at which time there also appears to be little if any difference between deaf individuals with and without CIs across a variety of cognitive domains (Figueras et al, 2008;Marschark, Spencer et al, 2015;Marschark, Paivio et al, 2016). As noted earlier, this finding has been suggested to reflect greater difficulty and differing goals of reading at the high school level (Archbold, 2015), the need for longer term interventions following cochlear implantation (Nittrouer & Caldwell-Tarr, 2016) or the involvement of alternative cognitive and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there is evidence that a greater signal to noise ratio is required for children with unilateral or mild HL compared to normal-hearing peers to understand speech (Bess et al 1986; Bovo et al 1988; Lieu 2004), placing them at a disadvantage in classrooms when trying to hear a teacher's voice above background noise (Crandell 1993). These children also tend to have difficulties with pragmatic and social skills, all of which may significantly affect learning and educational achievement (Moeller et al 2007; Cone et al 2010; Wolters et al 2011; Marschark et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…However, there also is emerging, convergent evidence that, on average, the early academic benefits seen in primary school are reduced or absent in secondary and postsecondary settings (Geers, Tobey, Moog, & Brenner, 2008; Harris & Terlektsi, 2011; Marschark, Shaver, Nagle, & Newman, 2015; see also Fitzpatrick et al, 2012). This situation may result, at least in part, from the greater complexity of materials and differing goals in secondary school (Archbold, 2015), premature cessation of interventions for CI users who show age-appropriate language and reading skills in primary school (Nittrouer & Caldwell-Tarr, 2016), lesser overlap between the language used at home and school in later grades (Chung, 2016), or because school-related skills increasingly are mediated by factors other than language level per se (H. Knoors, personal communication, May 19, 2016).…”
mentioning
confidence: 99%